2022
DOI: 10.3390/molecules27061865
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Antibacterial Sterols from Korean Wild Mushroom Daedaleopsis confragosa via Bioactivity- and LC-MS/MS Profile-Guided Fractionation

Abstract: As part of an ongoing natural product chemical research for the discovery of bioactive secondary metabolites with novel structures, wild fruiting bodies of Daedaleopsis confragosa were collected and subjected to chemical and biological analyses. We subjected the fractions derived from the methanol extract of the fruiting bodies of D. confragosa to bioactivity-guided fractionation because the methanol extract of D. confragosa showed antibacterial activity against Helicobacter pylori strain 51, according to our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Notably, demethylincisterol A 3 exhibits significant anti-tumor and antiinflammatory effects [31,32]. Studies have demonstrated that the rate of inhibition exhibited by demethylincisterol A 3 towards Helicobacter pylori is 11% greater than that of 100 µM quercetin [33]. Despite its recognized therapeutic potential, there has been limited research on its QS inhibitory effect against pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, demethylincisterol A 3 exhibits significant anti-tumor and antiinflammatory effects [31,32]. Studies have demonstrated that the rate of inhibition exhibited by demethylincisterol A 3 towards Helicobacter pylori is 11% greater than that of 100 µM quercetin [33]. Despite its recognized therapeutic potential, there has been limited research on its QS inhibitory effect against pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent investigations, we harnessed GNPS-guided isolation, leading to the discovery of four new madurastatin derivatives derived from the fungus Actinomadura sp. RB99 [32]. This outcome highlights the power of GNPS as an invaluable tool for discovering new natural compounds from natural sources.…”
Section: Introductionmentioning
confidence: 93%
“…This species has also garnered attention for its traditional uses, such as ornamental paper making, due to its unique textures and colors, showcasing its versatility beyond its ecological significance [24]. On the other hand, its pharmacological and medical importance has been overlooked aside from a few studies that have shown that this polypore fungus exhibits promising antibacterial, antifungal, and antioxidative activities [25][26][27].…”
Section: Introductionmentioning
confidence: 99%